The Voice Upstairs - Weymouth, Laura E. (New York : Margaret K. McElderry Books, 2023)
With the ability to see when a person's spirit leaves their body, Wilhelmina Price takes a job at her lifelong friend Edison's family estate to investigate a maid's death.
New YA Book Winter 2023.
Ages 14 up.
Grades 10-12.
Keywords: Ability -- Fiction; Supernatural; Mystery and detective stories; Death -- Fiction; Friendship -- Fiction; Detective and mystery stories; Supernatural; Novels; Detective fiction; Mystery fiction